Bendix MA-1A Time-of-Flight Mass Spectrometer - Bendix Corporation (1960)
Series of photographs depicting the Bendix MA-1A Time-of-Flight Mass Spectrometer and a female model. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation. Mass spectrometry is an analytical technique used to identify qualitatively and quantitatively the atomic and molecular composition of inorganic and organic materials by sorting ions according to their mass-to-charge ratios. Mass spectrometers consist of four basic parts: a handling system used to introduce the unknown sample into the equipment; an ion source, in which a beam of particles characteristic of the sample is produced; an analyzer that separates the particles according to mass; and a detector, in which the separated ion components are collected and characterized.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Women in advertising; Bendix Corporation; Mass spectrometers